IMPLEMENTASI AKUNTANSI BERBASIS MAQASHID SYARIAH: STUDI KASUS PADA PEMBIAYAAN DI BMT BINA INSAN SEJAHTERA JAMBI - Icha Pratiwi Saputri; Habriyanto; M. Maulana Hamzah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the application of maqashid-based Sharia accounting in microfinance practices at BMT Bina Insan Sejahtera Jambi. The study was motivated by the gap between the ideal concept of Sharia accounting and its practical application, particularly regarding transparency, accountability, fairness, and customer welfare. This study employs a qualitative approach using the case study method. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data presentation, and conclusion-drawing techniques. The findings indicate that the implementation of maqashid-based Islamic accounting at BMT Bina Insan Sejahtera Jambi has generally been carried out in accordance with Islamic principles, particularly in promoting fairness in financing, transparency in financial management, and social responsibility through the distribution of zakat, infaq, and sadaqah funds. The institution also demonstrates efforts to protect wealth (hifz al-mal), maintaining fairness in transactions and improving members’ well-being. However, several challenges remain, including limited human resources, the need to optimize accounting systems, and the need for stronger integration of maqashid syariah principles into operational practices. This study contributes to the development of Sharia accounting literature at the microfinance level and provides practical recommendations for strengthening maqashid Sharia-based governance in Sharia microfinance institutions.